2019
DOI: 10.1111/jasp.12595
|View full text |Cite
|
Sign up to set email alerts
|

Individuating information influences partisan judgments

Abstract: Three studies examined whether Democrats and Republicans expressed favoritism toward an ingroup political candidate, even when the candidates were presented as positive and bipartisan. Participants rated electability and traits, after reading party consistent (Passage 1) and positive, bipartisan information (Passage 2). Conservatism (Studies 1-3), the cognitive reflection test (Studies 2-3), and ingroup loyalty (Study 3) were examined. Republicans showed initially higher favoritism after the first passage. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Although we lack data that can directly explain this discrepancy, past literature suggests that there may be issues with the reliability and validity of Likert-type measures of attitudes in political prejudice research. For instance, Price-Blackshear et al (2019) found that an electability Likert-type scale and a semantic differential (i.e., different Likert-type measures of similar constructs) yielded different results within the same sample. In addition, these authors also found that the same semantic differential measure resulted in different findings when administered in two different samples drawn from the same population despite highly similar research designs and identical stimulus materials.…”
Section: Explaining Discrepancies Discrepancies Among Measures Of Aff...mentioning
confidence: 99%
“…Although we lack data that can directly explain this discrepancy, past literature suggests that there may be issues with the reliability and validity of Likert-type measures of attitudes in political prejudice research. For instance, Price-Blackshear et al (2019) found that an electability Likert-type scale and a semantic differential (i.e., different Likert-type measures of similar constructs) yielded different results within the same sample. In addition, these authors also found that the same semantic differential measure resulted in different findings when administered in two different samples drawn from the same population despite highly similar research designs and identical stimulus materials.…”
Section: Explaining Discrepancies Discrepancies Among Measures Of Aff...mentioning
confidence: 99%
“…In one, individuating information reduced people's tendency to rate an ingroup candidate as more electable than an outgroup candidate (Price-Blackshear et al, 2019). In a second, researchers examined when people will rely on individuating information (a politician's position on specific issue) vs. stereotypes (their party membership) when making assumptions about a politician's stance on other political issues (Crawford et al, 2011).…”
Section: The Role Of Individuating Informationmentioning
confidence: 99%
“…Further, some research has not replicated links between reflection and moral judgments (e.g., Attie & Knobe, 2017; Gawronski et al., 2017), politically liberal preferences (e.g. Price‐Blackshear et al., 2019), and belief in god (e.g., Sanchez et al., 2017). More research has found that the links between reflection and religiosity replicate in only some countries (Gervais et al., 2018) and religions (Byrd & Sytsma, In preparation).…”
Section: Reflection In Cognitive Science Of Philosophymentioning
confidence: 99%